Harmonisasi Kehidupan Sosial dan Ekonomi dalam Plurarisme Agama - Idwal B; Edi Sumanto (Sharia Economic and Management Business Journal (SEMBJ), 2022)
Religious harmony is an important part of every society in Indonesia and if you ignore this issue, it will have fatal consequences for human survival. Humans must uphold the values of religious diversity in Indonesia, because by living in harmony it has maintained the good name of the nation and state. As a Muslim community, it must maintain an attitude towards adherents of other religions, and vice versa, non-Muslim adherents must maintain an attitude with Muslim adherents. So that inter-religious harmony will be created, by taking care of each other and helping each other for the continuity of worship, it is also necessary to know that the Indonesian state consists of various tribes, languages, customs, and religions, so that the Indonesian nation is a pluralistic society. In the community of Air Petai Village with these various religions living side by side, of course there are problems that occur, both small and large. This feeling of suspicion is caused by an unnatural, prejudiced view of other groups that has been ingrained. Suspicion is also caused by a feeling of determinism that only the views of one's own group are correct and other groups are basically bad, so there is no place for an attitude that animates tolerance.